PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP STRES PADA LANSIA - Bahrir, Ina Nisrina; Komariah, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Stress is the external events and situations that burden the environment adaptability, individuals, particularly in the form of emotional and psychological burden, prolonged stress can be bad for the health of the elderly. Environment can support or interfere with the function of the physical and social circumstances occur due to lack of family role, then the role of the social environment that could cause conflicts and shocks tabe streess. Murottal Qur'an that contains some verses of the Qur'an to clear the heart and cleanse the soul elderly, especially for the elderly who are experiencing stress. This research quantitative research methods approach pre asExperiment with one group pretest - Posttest. The amount of the total sample of 40 respondents. This research subject is old egg who wexperience stress in UPT. Social services elderly Bondowoso. The sample used purposive sampling. Measurement data using stress questionnaire, observation before and after Murottal Qur'an. analysis using the Wilcoxon Signed Rank Test. The results showed before doing therapy murottal Qur'an many people. hare experience severe stress as muchas (26 seniors), moderate stress (14 seniors), and mild stress (0), after doing therapy murottal Qur'an stress on elderly, it decreate to be moderate stress (40 old egs), stress (weight 0), and mild stress (0). In hypothesis testing using the Wilcoxon Signed Rank Test results were obtained sig. p value = 0.000, which means p value <0.05 So HI accepted. The conclusion from this study resereh,the Qur'an murottal therapy candecrease elderty stressKeywords: Knowledge, Murottal Qur'an, Stress At Elderly.